EMBRACING THE ABSURD CONDITION OF EXISTENCE IN SAMUEL BECKETT’S ENDGAME CHARACTERS - Restu Dwi Gilang Permana; Dewi Kustanti (Saksama, 2022)
This research initially attempts to determine characteristics and characterization of the characters; Clov, Hamm, Nagg, and Nell, as well as how it represented the concept of absurdity. The play involves a critical review and otherwise, more appropriately, a conception addressed toward the audience or reader. As a result, researcher chooses to utilize a moral-philosophical approach to conduct this research. As according Camus, absurdity cannot be fully investigated. It is only determined by utilizing the method for explaining the concept of absurdity. Several concepts are represented throughout the drama by the characters' acts, utterances, and thoughts. Those ideas include monotony routine, meaningless circumstances, and the end. Depending to Camus' theory of absurdity, those concepts might well be classified as a representation of such the absurdity concept. The author's condemnation on existence of humankind in the play script may be recognized by considering the perspective regarding Camus' absurdity concept as the characteristics and characterization of characters represents the absurdity concept.